Consumption smoothing and liquidity income redistribution - Giuseppe Bertola; Winfried Koeniger (Goethe University Frankfurt, Center for Financial Studies (CFS), 2006)
We show theoretically that income redistribution benefits borrowingconstrained individuals more than is implied by standard relative-income and uninsurable-risk considerations. Empirically, we find in international opinion-survey data that younger and lower-income individuals express stronger support for government redistribution in countries where consumer credit is less easily available. This evidence supports our theoretical perspective if such individuals are more strongly affected by tighter credit supply, in that expectations of higher incomes in the future increase their propensity to borrow.
urn:nbn:de:hebis:30-38088
Keywords: E21; 330; Consumption; Smoothing